Measuring the experience of off-price fashion shopping: scale development and validation. Issue 4 (11th June 2018) - Mortimer, Gary; Fazel-e-Hasan, Syed Muhammad; O'Donnell, Kathleen A.; Strebel, Judi
Abstract : Purpose: Off-price fashion retailers are expected to dominate the retail sector over the next five years. Surprisingly, selling excess designer labels, in what some describe as a disorganized manner, appeals to certain shoppers who enjoy the "thrill of the hunt." Recent research conceptualized consumers, whose motivation for, and outcomes from, fashion shopping set them apart from previously reported shopper types. Referred to as "Sport Shoppers, " they view fashion shopping as an achievement domain. The purpose of this paper is to quantify such shoppers through the development of a valid psychometric scale. Design/methodology/approach: Four studies, comprising depth interviews and online surveys, across two countries were employed to develop a three-dimensional scale of the sport shopping experience. Factor analyses and structural equation modeling were used to analyze and test a theoretically hypothesized model. Findings: Study 1 generated items aligned to the three theoretical dimensions of the sport shopping experience. Study 2 confirmed reliability and factor structure of the psychometric scale. Study 3 provides evidence of convergent and discriminant validity with previous shopper types. Finally, Study 4 demonstrates nomological validity through a theoretically hypothesized model of the sport shopping experience. Originality/value: This is the first study to employ achievement goal theory in a consumer behavior context to delineate an emergent shopper type. The developed scale is the most comprehensive, multi-dimensional measure of the experience of this new consumer type. As such, it represents a valuable contribution to fashion retail and consumer behavior literature. The scale enables practitioners to quantify target markets and identify relationships to other factors, such as overall satisfaction and brand repurchase intentions.